Cardiovascular comorbidity in patients with chronic obstructive pulmonary disease: echocardiography changes and their relation to the level of airflow limitation - Buklioska Ilievska, Daniela; Minov, Jordan; Kochovska Kamchevska, Nade; Prgova Veljanova, Biljana; Petkovikj, Natasha; Ristovski, Vladimir; Baloski, Marjan (Scientific Foundation SPIROSKI, 2019)
Objective. To compare frequency of echocardiographic changes in patients with chronic obstructive pulmonary disease (COPD) and non-COPD controls and to assess their relation to the level of airflow limitation. Methods. Study population included 120 subjects divided in two groups. Group 1 included 60 patients with COPD (52 male and 8 female, aged 40 to 80 years) initially diagnosed according to the actual recommendations. Group 2 included 60 subjects in whom COPD was excluded serving as a control. The study protocol consisted of completion of a questionnaire , pulmonary evaluation (dyspnea severity assessment, baseline and post-bronchodilator spirometry, gas analyses, and chest X-ray) and two dimensional (2D) Doppler echocardiography. Results. We found significantly higher mean right ventricle end-diastolic dimension (RVEDd) in COPD patients as compared to its dimension in controls (28.0 Â± 4.8 vs. 24.4 Â± 4.3; P = 0.0000). Pulmonary hypertension (PH) was more frequent in COPD patients than in controls (28.0 Â± 4.8 vs. 24.4 Â± 4.3; P = 0.0000) showing linear relationship with severity of airflow limitation. The mean value of left ventricular ejection fraction (LVEF%) was significantly lower in COPD patients than its mean value in controls (57.4 Â± 6.9% vs. 64.8 Â± 2.7; P = 0.0000) with no correlation with severity of airflow limitation.       Conclusion. Frequency of echocardiographic changes in COPD patients was significantly higher as compared to their frequency in controls in the most cases being significantly associated with severity of airflow limitation. Echocardiography enables early, noninvasive, and accurate diagnosis of cardiac changes in COPD patients giving time for early intervention. Key words: airflow limitation, chronic obstructive pulmonary disease, Doppler echocardiography, pulmonary hypertension, ventricular dysfunction.